Komatiites From Mantle Transition Zone Plumes - Wyman, Derek (Frontiers in Earth Science, 2020)
During the Archean, episodic volcanism commonly included both plume- and arc-type magmatism, raising the issue of a possible link between “bottom up” and “top down” geodynamic processes. Rather than plume-initiated subduction, the best-preserved cratons demonstrate that komatiitic magmatism postdated at least some of the subduction linked volcanism. Several factors suggest that komatiite-generating plumes were sourced in the mantle transition zone. Komatiites contain 0.6 wt.% or more H2O, which is contrary to earlier predictions for plume ascent through the transition zone. Geodynamic reconstructions indicate that multiple subducted slabs penetrated the transition zone in the region of future plume ascent and the related trench configurations limit the size of any associated plume heads. The implied plume head sizes are inconsistent with those required for a plume to ascend from the core-mantle boundary but match those predicted for plumes sourced from the lower transition zone. Transition zone plumes have mainly been advocated for in post-Archean “big wedge” scenarios involving subducted slabs that stall at the base of the transition zone but they are also an outcome of the “basalt barrier” featured in some geodynamic models for the Archean and early Proterozoic. The latter models suggest the basaltic components of Archean subducted slabs were too buoyant to descend into the lower mantle and formed a boundary layer that isolated the upper mantle and lower mantle on the early Earth, except in times of mantle overturns. The basalt barrier was a significant thermal boundary layer that, in principle, could act as the nucleation site of upwelling plumes anywhere on the globe. The evidence discussed here, however, suggests that the mainly peridotitic mantle upwellings were enhanced by the nearby injection of closely associated slabs into the transition zone. The simplicity of the Mantle Transition Zone (MTZ) plume-forming mechanism ensured that komatiites could be generated throughout the Archean even as Earth moved toward a regime involving modern-style subduction, globe-encompassing oceanic ridge systems and tectonic plates. The distinctive geodynamic setting of Gorgona Island produced relatively low-temperature komatiites at the only place along the margin of North and South America where it was possible to reproduce the bowl-like subduction configurations commonly associated with their Archean and Paleoproterozoic counter parts.